2022
DOI: 10.1007/s10554-022-02533-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of left atrial wall thickness and pulmonary vein sizes on the acute procedural success of atrial fibrillation ablation

Abstract: Nowadays, a novel contact-force guided ablation technique is used for enclosing pulmonary veins in patients with atrial fibrillation (AF). We sought to determine whether left atrial (LA) wall thickness (LAWT) and pulmonary vein (PV) dimensions, as assessed by cardiac CT, could influence the success rate of first-pass pulmonary vein isolation (PVI). In a single-center, prospective study, we enrolled consecutive patients with symptomatic, drug-refractory AF who underwent initial radiofrequency catheter ablation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“… The first‐pass isolation (FPI) rate was defined as the presence of the entrance and exit block of the PV after completing a first circumferential ablation in all four PVs 12 Total procedure time. Rate of major complications including cardiac tamponade/pericardial effusion, PV stenosis, thromboembolism, groin bleeding required transfusion, phrenic nerve paralysis, and atrioesophageal fistula 13 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… The first‐pass isolation (FPI) rate was defined as the presence of the entrance and exit block of the PV after completing a first circumferential ablation in all four PVs 12 Total procedure time. Rate of major complications including cardiac tamponade/pericardial effusion, PV stenosis, thromboembolism, groin bleeding required transfusion, phrenic nerve paralysis, and atrioesophageal fistula 13 …”
Section: Methodsmentioning
confidence: 99%
“…(2) The first-pass isolation (FPI) rate was defined as the presence of the entrance and exit block of the PV after completing a first circumferential ablation in all four PVs. 12 (3) Total procedure time.…”
Section: Secondary Outcomesmentioning
confidence: 99%
“…In the recently published study by Boussoussou et al, the authors revealed that RSPV diameter is associated with a higher rate of successful right-sided first-pass isolation [73]. Additionally, according to another recent paper, only the larger LA volume index and variant PVs anatomy are independently associated with increased risk of AF recurrence [74].…”
Section: Pulmonary Veins Geometrymentioning
confidence: 98%
“…A local impedance drop more than 21.80 ohms on the anterior wall and more than 18.30 ohms on the posterior wall significantly increased the probability of creating a successful lesion [26]. Boussoussou M et al [27] found that LA wall thickness did not influence the first-pass isolation rate during PVI guided by the modified CLOSE protocol (AI 400 on the posterior wall and 500 on the anterior wall, CF 10-40 g). Only the diameter of the right superior PV was associated with the success rate of right-sided first pass isolation, as a wider right superior PV diameter led to an easier first-pass isolation.…”
Section: The Success Rate With Different Application Settingsmentioning
confidence: 99%